Random Individual Facades, Informal Buildings and Aesthetic Chaos: How Can Urban Architecture Help - The Case of Tirana, Albania - Biqiku, Klea (European Journal of Multidisciplinary Studies, 2022)
In recent years, the situation of informal buildings in our country it is getting serious. There is ample evidence proving that many informal buildings have been constructed in sites decided by the entrepreneurs/ owners of the land not following any urban planning logic/ analyses, supposedly as something like that does not formally exists yet. There seem to be a correlation and causation relationship between this phenomenon and encroachment on the urban space and the loss of the archetype. Informal building has taken many definitions in Albanian context from extensions of floors and or interventions on facades to the extreme but significant cases of the occupation of public spaces. The spontaneity of the process has led to the creation of an urban chaos as far as the relationships of the citizen with urban architecture leading to a chaotic urban aesthetics. Tirana is one of developing cities that has had a “constructions boom.” The benefits as far as employment and services that “the construction boom” brought about were welcomed with such a high enthusiasm that the implications of having, in certain cases, entire areas with informal buildings have been much neglected. This unchecked phenomenon is putting in danger the heritage values of the city and their identity/archetype. The diversity has not led to any certain aesthetics, with facades lacking the minimum of basic composition and design criteria of urban architecture principles, therefore causing an irregularity on the urban areas. This is a point to raise the hypotheses: Can Urban Architecture still help with minimal cost and damage? Is there still possibility for making things right? Will time and Budgetary issues become an issue? Does political will has to be taken into account? Should Citizen Participation in decision making in Urban Architectural Improvements have a role to play and what will the instruments for this Citizen Participation be? This research paper does represent a work in progress. It analyzes these interventions and look at the impact that they have on urban context and its aesthetics and provide tentative suggestions on how to improve the current situation. The case referred to in the paper is more than an exercise to help us to reflect and to propose novel approaches.